2013
DOI: 10.47338/jns.v2.15
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Surgical Correction of Anorectal Malformation Associated with Rectourinary Fistula in Male Neonates

Abstract: Introduction: The treatment of children affected by anorectal malformations (ARM) is characterized by some unsolved problems. The three-stage surgical correction has been known to be most effective in preventing complications, but recently new approaches have been proposed. We describe our experience with the newer approaches.Methods: Twenty three male newborns, affected by ARM and recto-urinary fistula, were treated in 2 different centers in 8 years. Nineteen neonates (birth weight 2.4 - 3.5 kg) received a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Out of 63 patients of high variety, 53 (84.12%) were males and 10 (15.87%) were females, and out of 37 patients of low type, 16 (43.24%) were males and 21 (56.75%) were females. Thus, male children have a higher chance of having a high variety of lesions than female children [5,6,7]. In the present study, we observed that children with a high type of anomaly have an increased incidence of associated anomalies.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Out of 63 patients of high variety, 53 (84.12%) were males and 10 (15.87%) were females, and out of 37 patients of low type, 16 (43.24%) were males and 21 (56.75%) were females. Thus, male children have a higher chance of having a high variety of lesions than female children [5,6,7]. In the present study, we observed that children with a high type of anomaly have an increased incidence of associated anomalies.…”
Section: Discussionsupporting
confidence: 52%
“…The crux of proper management and future results mainly depends upon the exact diagnosis of the type of anomaly, identification of associated fistulous communications, and the presence of other congenital anomalies [1][2][3]. The National Institutes of Health, United States Department of Health, and Human Services stated that about one in every 5,000 neonates is born with anorectal malformations (ARMs), with an increased preponderance among males [4][5][6]. Various surgical procedures have been adopted depending on the level of the distal rectal pouch and its relation to the puborectalis sling.…”
Section: Introductionmentioning
confidence: 99%
“…[2,8,9,10] These patients who do not return at 6-8 weeks for the definitive procedure have lower chances of early restoration of defecation reflex. [1,2,6,[11][12][13][14][15][16] As per Pena, primary definitive surgery can be done in male neonates depending on surgeons' experience and condition of neonates, provided the neoanus is placed well within the sphincter muscle complex. [17] Nagdeve et al reported good continence with primary PSARP.…”
Section: Discussionmentioning
confidence: 99%
“…The cause has not been fully elucidated but it is likely to be multifactorial and include genetic and environmental factors [6,7]. Males are more affected than females and may occur as a single abnormality or a combination of abnormalities [8][9][10]. ARMs have been reported to be associated with other congenital anomalies in up to 70% of cases [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Males are more affected than females and may occur as a single abnormality or a combination of abnormalities [8][9][10]. ARMs have been reported to be associated with other congenital anomalies in up to 70% of cases [8,9,11]. The final prognosis and quality of life for children with ARMs depend, to a large extent, on the presence and severity of these associated anomalies [11].…”
Section: Introductionmentioning
confidence: 99%